Saints, Sacred Trees, and Snakes: Popular Religion, Hierotopy, Byzantine Culture, and Insularity in Cyprus during the Long Middle Ages - Kyriacou, Chrysovalantis (Religions, 2021)
The holiness of sacred spaces is expressed through the creative synthesis and performance of different symbolic or iconic elements. This article concentrates on the medieval church of Ayios Iakovos in Nicosia, Cyprus. Dedicated to Saint James the Persian, the church became, by the 1600s, a shared shrine for Christians of different denominations (Orthodox, Maronites, and Latins) and Muslims. The aim of this article is to investigate in an interdisciplinary way the formation, adaptation, and negotiation of insular religious identities in relation to Ayios Iakovos’ hierotopy, official and popular religious practices, and the appropriation of Byzantine culture. The components in the creation of this sacred space reflect long-term contact between Cyprus and Greater Syria, constructing an inclusive religious environment with its own insular characteristics. It will be argued that these characteristics were shaped by global, regional, and local developments, including trade, pilgrimage, war, and environmental changes. Being in dialogue with recent scholarship on mixed sacred sites, this case study stresses the importance of interconnectivity and mobility in the creation of shared places of worship. It also shows that phenomena of religious co-existence and syncretism do not always result in homogenisation but maintain distinct group identities.